A hermeneutic phenomenological interpretation of the lived experiences of nursing students with regards to death and dead bodies - Chinomso Ugochukwu Nwozichi (Wolters Kluwer Medknow Publications, 2015)
Background: The experience of death and dead bodies usually generates psychological reactions among nursing students. This study attempted to interpret the lived experiences of nursing students with regards to death and dead bodies. Materials and Methods: Using a hermeneutic phenomenological approach, texts from the reflective diaries of nursing students were interpreted in relation to their experiences with death and dead bodies during their clinical postings. The interpretation involved three stages: Naive reading, structural analysis, and comprehensive understanding. Reflective diaries of 12 students met the inclusion criteria and thus were used for the interpretation. Results: Three themes emerged from the structural analysis; (i) personal reflection on harsh reality, (ii) unavailability of required support and abandonment, (iii) identification of individual strength and weakness based on experience. Conclusion: Nursing students expressed some emotional reactions that require the attention of their instructors. Nurse educators should always be available to support the students during clinical exposures. End-of-life components of the nursing curriculum should be improved.